Frank Lloyd Wright in the Soviet Union - Brian A. Spencer (Проект Байкал, 2017)
In 1937 the First All-Union Congress of Soviet Architects was held in Moscow. The congress brought  architects from all areas of the  Soviet Union. Under the auspices of Vsesoiuvnoe Obshchestvo Kul'turnoi Sviazi s zagranitsei (VOKS) it invited international architects from Europe and North and South America.  The Organizing Committee of the Union of Soviet Architects invited Frank Lloyd Wright from the United States. Frank Lloyd Wright presented his philosophy and exhibited his work, specifically his designs for the weekend home for E. J. Kaufmann "Fallingwater" and the drawings for the S.C. Johnson Administration. Frank Lloyd Wright's presentation did not focus heavily on the architecture but, rather the spirit of the Russian and Soviet vision.